ANALISIS MODEL PREDIKSI KESULITAN KEUANGAN DAN KEPAILITAN PADA USAHA PERBANKAN DI INDONESIA BERDASARKAN CAMEL, RASIO ALTMAN DAN BMPK - Aziz, RZ Abdul (Jurnal Manajemen dan Keuangan, 2008)
The objective of this research is to create models of one, two, or three years before the financial difficulties, bankrupty, and survival. The accuracy of the models in predicting is then tested. The models are created based on eleven financial ratios, which are, CAR, Bad Debt Ratio, Net profit Margin, ROA, BOPO, Net Call Money to Current Assets, LDR, Working Capital to Total Assets, Book Value to Total Liabilities, Retained Earning to Total Assets, and BMPK. The method used for categorizing bank bankruptcy, financial difficulties, and survival is that of CAMEL method. In creating the model, statistical testing device of multiple discriminant analysisi is used.The result of the research shows that the rations that are related to the discriminant model of three years before financial difficulties, bankruptcy, and survival are those of CAR, and Book Value of Equity to Total Liabilities, for the model of two years before financial difficulties, bankrupty, and survival the rations are those of CAR, Book Value of equity to total liabilities, and Bed Debt Ratio, and as for the one year before financial dificulties, bankrupty, and survival there are only two ratios, which are BOPO and Book Value of Equitymto Total Liabilities.The models formed for one, two, and three years before financial difficulties, bankruptcy, and survival have a good level of accuracy in predicting. Therefore, it can be said that the three models can be used as one of the anticipating devices.Keyword : LDR, Quick Ratio, Asset to Loans Ratio, Non Performing Loans, CAR, Capital Ratio, Deposit Ratio, ROE, ROA, NIM, BOPO and NPM